Reflective Pedagogy, Cosmopolitanism, and Critical Peace Education for Political Efficacy:: A Discussion of Betty A. Reardon’s Assessment of the Field - Reardon, Betty; Snauwaert, Dale (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
In a recent publication entitled ”Concerns, Cautions and Possibilities for Peace Education for Political Efficacy” Betty Reardon reflects on the state of peace education and offers a brilliant reaffirmation and further elaboration of the central importance and nature of a pedagogy of reflective inquiry for a comprehensive/critical peace education. Betty Reardon is an internationally renowned peace scholar and peace educator. She has been instrumental in the establishment of peace education institutions and programs around the world. Her work has defined the fields of peace studies and peace education. The purpose of this paper is to discuss her recent assessment and elaboration. Inparticular, the connection between cosmopolitanism and reflective pedagogy will be explored in greater detail, in addition to the posing of further questions for inquiry related to the relationship between dialogue, conceptual clarity, philosophical frameworks, diversity and reflective pedagogy.